Green and chemical synthesis of silver nanoparticles: Study of biological properties and toxicity concerns related to chemically synthesized nanoparticles - Salunkhe, Pradnya; Borse, Tushar; Pathade, Girish; Patil, Dhanashri (Journal of Neonatal Surgery, 2025)
Metallic nanoparticles, particularly silver nanoparticles, are widely used in science, engineering, and medicine due to their small size. However, conventional synthesis methods pose biological hazards, prompting the development of environmentally friendly methods like green synthesis using plant-derived components. Present study used eco-friendly, cost efficient and easy method for synthesis of silver nanoparticles (AgNPs) using Withania somnifera extracts as reducing and capping agents. In another approach, chemical synthesis of AgNPs has been carried out using tri-sodium citrate and polyethylene glycol as reducing agents. Measurement on UV-Vis absorption spectroscopy at 415 nm confirmed the synthesis of AgNPs in the solution. Both the AgNPs were tested for their antibacterial properties against Bacillus subtilis, antioxidant and antifungal properties against A. niger. The chemically synthesized AgNPs were tested on the seed germination of Zea mays for detecting their toxic effect. Moreover, the treated plantlets were also evaluated for their protein and chlorophyll content and results confirmed that as the concentration of chemically synthesized AgNPs increases the growth of the Zea mays plantlet decreases